Clinicopathologic Profile and Review of Breast Cancer Patients in a Resource Limited Setting: The Unimedthc Experience - Okunnuga, Ndidi Aishat; Nweke, Michael Chukwugozie; Pelemo, Olumuyiwa Eyitayo; Inigbedion, Clement Erakhuemen; Osho, Evelyn Salewa; Okunnuga, Adetokunbo Adedotun; Osho, Patrick Olarenwaju (British Journal of Healthcare and Medical Research, 2022)
Background: breast cancer is the commonest cancer found amongst women. It is the leading cause of cancer death in nigerian women. The burden of breast cancer is high among women of all age groups in nigeria. The clinical and pathological presentation of breast cancer among women in ondo state, south west nigeria has its peculiarities with the limited available resources. Objective: to evaluate the clinico-pathological factors of breast cancer. To access the treatment profile and the overall outcome of patients with breast cancer. Design: the study is a descriptive analytical hospital based study from case records of patients attending outpatient clinic at a tertiary hospital facility in akure, ondo state. South west, nigeria. Method: a total of 312 cases were included for the analysis and duration was from march 2013 to april 2018. Data with respect to demographic status, histological status, tumour stage, treatment offered and outcome was collated and collected from the records of patients attending the oncology out- patient clinic at university of medical science teaching hospital akure, ondo state south west nigeria. Result: a total number of 312 patients with breast cancer were analyzed. The most common age group was 33 years to 42 years, with a mean age of 47.8 years. Many of the participants 57.7% had secondary education. 84.3% of the women were married and 35.9% had parity of 3. The commonest histological type is the invasive ductal carcinoma. 4.5% resided outside akure. Many of the participants 44.2% presented with stage 3 of the disease and the commonest site of metastasis was the lungs. Conclusion